Climate Change News Reporting in Kenya: Journalists as Curators - Agalo, Rose; Day, Peter; Ronoh , Lamek; Otieno, Millicent (International Journal of Professional Practice, 2024)
The media’s increased coverage of climate change has raised global climate change awareness. However, limited resources, and low access to information and scientific expertise have constrained climate change news coverage in Kenya. Competing news priorities and the perceived complexity of climate change issues have further contributed to this limitation. This study investigated the role of journalists in reporting climate change news in Kenya. The study employed a mixed research design where 50 questionnaires were administered to practicing journalists from four media houses based in Kenya; namely, NTV, Citizen TV, Nation, and Standard newspapers, who were purposively selected. Additionally, the researcher collected qualitative data from ten journalists from the 50 surveyed. Descriptive and thematic analysis was conducted to interpret the data according to the research questions. The findings revealed a shifting media landscape in climate journalism, highlighting the necessity for journalists to undergo specialized training in climate reporting. The findings of this study will contribute to the achievement of Sustainable Development Goal 13 on climate action.